Analysis of Physical Risks in the Property Insurance Underwriting Process at PT. Asuransi Umum XYZ Jakarta - Edison Edison; Suhartono Suhartono; Antonius Anton Lie (International Journal Labs, 2026)
Climate change has become a critical factor influencing financial and insurance sectors, particularly through physical risks affecting property assets. Indonesia, with its high exposure to hydrometeorological hazards, presents a unique context for analyzing the integration of physical risk into property insurance underwriting. This study aims to explore how physical risk is understood, assessed, and incorporated into the underwriting decision-making process at a national general insurance company, referred to as Company XYZ. A qualitative case-study approach was employed, combining primary data from in-depth interviews and written responses from ten cross-functional informants with secondary data from internal company documents, claims data, and annual reports from 2020–2025. Thematic analysis was used to interpret patterns in the data. Results indicate that physical risks, particularly floods and extreme weather, are recognized as major factors shaping underwriting decisions, with integration occurring across marketing, underwriting, reinsurance, risk engineering, and claims functions. While historical-data-based approaches dominate current practice, forward-looking assessments are increasingly considered necessary. The study concludes that effective incorporation of physical risk requires enhanced data quality, professional judgment, and advanced analytical tools to support adaptive and sustainable underwriting. Findings provide practical insights for insurance practitioners and contribute to understanding organizational responses to climate-related financial risks.